2019
DOI: 10.1016/j.addbeh.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and cannabis co-use and interrelatedness among adults

Abstract: Cannabis and tobacco co-use is prevalent, but consensus regarding the reasons for co-use among adults and the degree of interrelatedness between these substances is lacking. Reasons for co-use have been explored with younger users, but little data exists for more experienced users with entrenched patterns of co-use. The goal of this study was to examine characteristics and patterns of cannabis-tobacco co-use among adults in the Southeastern United States (US), where there is a legal landscape of generally rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 61 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…Marijuana usage was also found to be intrinsically linked with tobacco use and cessation. While no prior studies have investigated the interaction of marijuana and tobacco in HNC patients, multiple studies in the general population have demonstrated that co‐use of marijuana and tobacco is associated with higher nicotine dependence 22,23 which can make cessation challenging. There is a clear requirement for future studies to investigate whether addressing marijuana cessation will improve rates of tobacco abstinence among newly diagnosed HNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana usage was also found to be intrinsically linked with tobacco use and cessation. While no prior studies have investigated the interaction of marijuana and tobacco in HNC patients, multiple studies in the general population have demonstrated that co‐use of marijuana and tobacco is associated with higher nicotine dependence 22,23 which can make cessation challenging. There is a clear requirement for future studies to investigate whether addressing marijuana cessation will improve rates of tobacco abstinence among newly diagnosed HNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…From 18% to 39% of adults who used tobacco in the past month in the United States also used marijuana, and 69% to 78% of marijuana users used tobacco in the past month (4,5). Recent longitudinal research showed that marijuana users were more likely to start smoking cigarettes, continue to smoke cigarettes over time (as opposed to quitting), and relapse back to cigarette smoking once they had quit (6). Daily use of marijuana is associated with a 3.6-fold increase in nicotine dependence (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Social disadvantage is related to increased rates of concurrent use of tobacco and cannabis [57]. Concurrent daily tobacco and cannabis use has been found to be high (40–78%) as cannabis users often mix their cannabis with tobacco for smoking [8]. Concurrent use has been linked to an increased risk of and higher levels of nicotine dependence, poorer health outcomes and greater difficulty when quitting [811].…”
Section: Introductionmentioning
confidence: 99%